Beyond pure reason : Ferdinand de Saussure's philosophy of language and its early romantic antecedents - Gasparov, B. (University seminars/Leonard Hastings Schoff memorial lectures., 2013)
The Swiss linguist Ferdinand de Saussure (1857?1913) revolutionized the study of language, signs, and discourse in the twentieth century. He successfully reconstructed the proto-Indo-European vowel system, advanced a conception of language as a system of arbitrary signs made meaningful through kinetic interrelationships, and developed a theory of the anagram so profound it gave rise to poststructural literary criticism. The roots of these disparate, even contradictory achievements lie in the thought of Early German Romanticism, which Saussure consulted for its insight into the nature of meaning.